.#isoverparty. The Consequences of Brand Boycotts for Brands in the Social Media Environment After Russia’s Invasion in Ukraine - Katarzyna Sanak-Kosmowska (Journal of Marketing and Consumer Behaviour in Emerging Markets)
This study investigated social-media-based anti-brand communication. Guided by consumer boycotts and brand cancellation theory, the author conducted a qualitative study based on content analysis of tweets about 59 international brands that remained in Russia after the invasion in February 2022. The research was conducted on Twitter between August 10 and 17, 2022. The study aimed to determine whether brands that have decided to stay in Russia are still exposed to negative WoM, calls for a boycott or brand cancellation after 6 months since the war began. The obtained results made it possible to identify the number of tweets and their content and sentiment. They also showed the dynamics of negative WoM publications on social media and their character. The practical implications are the following: brands exposed to consumer boycotts, depending on their business goals, may decide to adopt a "wait-out" strategy.